Spatiotemporal Measurement of Osmotic Pressures by FRET Imaging. (3rd February 2021) - Zhang, Wenbo; Bertinetti, Luca; Blank, Kerstin G.; Dimova, Rumiana; Gao, Changyou; Schneck, Emanuel; Fratzl, Peter
Abstract: Osmotic pressures (OPs) play essential roles in biological processes and numerous technological applications. However, the measurement of OP in situ with spatiotemporal resolution has not been achieved so far. Herein, we introduce a novel kind of OP sensor based on liposomes loaded with water‐soluble fluorescent dyes exhibiting resonance energy transfer (FRET). The liposomes experience volume changes in response to OP due to water outflux. The FRET efficiency depends on the average distance between the entrapped dyes and thus provides a direct measure of the OP surrounding each liposome. The sensors exhibit high sensitivity to OP in the biologically relevant range of 0–0.3 MPa in aqueous solutions of salt, small organic molecules, and macromolecules. With the help of FRET microscopy, we demonstrate the feasibility of spatiotemporal OP imaging, which can be a promising new tool to investigate phenomena involving OPs and their dynamics in biology and technology. Abstract : A novel osmotic pressure sensor based on liposomes loaded with FRET dyes is developed, which experience volume changes responding to osmotic pressure due to water outflux through their semipermeable membrane. With FRET microscopy, measurement of osmotic pressures in situ with spatiotemporal resolution is demonstrated, which has not been achieved so far.